Contrasted geographical distribution of N2 fixation rates and nifH phylotypes in the Coral and Solomon Seas (southwestern Pacific) during austral winter conditions. Issue 11 (2nd November 2015) - Bonnet, Sophie; Rodier, Martine; Turk‐Kubo, Kendra A.; Germineaud, Cyril; Menkes, Christophe; Ganachaud, Alexandre; Cravatte, Sophie; Raimbault, Patrick; Campbell, Ellen; Quéroué, Fabien; Sarthou, Géraldine; Desnues, Anne; et al.
Abstract: Biological dinitrogen (N2 ) fixation and the distribution of diazotrophic phylotypes were investigated during two cruises in the Coral Sea and the Solomon Sea (southwestern Pacific) during austral winter conditions. N2 fixation rates were measurable at every station, but integrated (0–150 m) rates were an order of magnitude higher in the Solomon Sea (30 to 5449 µmol N m −2  d −1 ) compared to those measured in the Coral Sea (2 to 109 µmol N m −2  d −1 ). Rates measured in the Solomon Sea were in the upper range (100–1000 µmol N m −2  d −1 ) or higher than rates compiled in the global MARine Ecosystem biomass DATa database, indicating that this region has some of the highest N2 fixation rates reported in the global ocean. While unicellular diazotrophic cyanobacteria from group A (UCYN‐A1 and UCYN‐A2) and the proteobacteria γ ‐24774A11 dominated in the Coral Sea and were correlated with N2 fixation rates ( p  < 0.05), Trichodesmium and UCYN‐B dominated in the Solomon Sea and were correlated ( p  < 0.05) with N2 fixation rates. UCYN‐A were totally absent in the Solomon Sea. The biogeographical distribution of diazotrophs is discussed within the context of patterns in measured environmental parameters. Key Points: N2 fixation is reported for the first time in the Solomon Sea and is among the highest of the ocean N2 fixation rates are 20 times higher in the Solomon Sea compared with the Coral Sea UCYN‐A/γ‐24774A11 dominate in the Coral Sea; Trichodesmium/UCYN‐B dominate in the Solomon Sea